2021
DOI: 10.3390/antibiotics10040455
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Antibiotic Prescriptions in Patients with Acute Lower and Upper Respiratory Tract Infections—A Case-Control Study

Abstract: : Background: The goal of the present study was to estimate the prevalence of patient and physician related variables associated with antibiotic prescriptions in patients diagnosed with acute lower and upper respiratory tract infections (ALURTI), treated in general practices (GP) and pediatric practices, in Germany. Methods: The analysis included 1,140,095 adult individuals in 1237 general practices and 309,059 children and adolescents in 236 pediatric practices, from the Disease Analyzer database (IQVIA), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The Disease Analyzer database is composed of sociodemographic, diagnosis, and prescription data obtained from general and specialized practices in Germany. Although this database covers only approximately 3-4% of the private practices in Germany, it has previously been demonstrated to be representative and has been widely used for epidemiological studies in recent years [23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…The Disease Analyzer database is composed of sociodemographic, diagnosis, and prescription data obtained from general and specialized practices in Germany. Although this database covers only approximately 3-4% of the private practices in Germany, it has previously been demonstrated to be representative and has been widely used for epidemiological studies in recent years [23][24][25].…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany [ 16 ]. Finally, this database has already been used in previous studies focusing on antihypertensive therapy [ 17 , 18 ] as well as respiratory infections [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although most RTIs are viral, nearly 70% of patients receive antibiotic therapy, which is unjustified as there is no evidence that its use will prevent bacterial superinfection. Such irrational therapy can even lead to harm as it contributes to increased antibiotic resistance and exposes patients to adverse effects (9)(10)(11) . Symptomatic treatment with antipyretic and analgesic agents, antitussives, expectorants, mucolytics and decongestants is recommended for viral infections.…”
Section: Treatment Guidelines For Respiratory Tract Infectionsmentioning
confidence: 99%